2014
DOI: 10.1093/gastro/gou053
|View full text |Cite
|
Sign up to set email alerts
|

Specimen retrieval approaches in patients undergoing laparoscopic colorectal resections: a literature-based review of published studies

Abstract: Objective: To review the published studies reporting various specimen retrieval incisions being used by colorectal surgeons in patients undergoing laparoscopic colorectal resections (LCR).Methods: Standard medical electronic databases were searched to find relevant articles and a summary conclusion was generated.Results: There were 43 studies reporting various approaches used for the purpose of specimen retrieval in 2388 patients undergoing LCR. The most common approaches were periumbilical midline incision (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 52 publications
(29 reference statements)
0
12
0
Order By: Relevance
“…[14] And with the development of surgery technique and instrument, the laparoscopic-assisted colorectal surgery was performed more and more extensive in the treatment of colorectal cancer with the advantages of overall survival, disease free survival faster recovery and shorter hospital stays. [15] However, the laparoscopic-assisted colorectal surgery also has its disadvantages such as relative long operation time and long training period for surgeon. [16] …”
Section: Discussionmentioning
confidence: 99%
“…[14] And with the development of surgery technique and instrument, the laparoscopic-assisted colorectal surgery was performed more and more extensive in the treatment of colorectal cancer with the advantages of overall survival, disease free survival faster recovery and shorter hospital stays. [15] However, the laparoscopic-assisted colorectal surgery also has its disadvantages such as relative long operation time and long training period for surgeon. [16] …”
Section: Discussionmentioning
confidence: 99%
“…MEDLINE and Embase will be searched from inception to the 1 st of August 2021 for observational and interventional studies written in English including patients who benefited from minimally invasive colorectal surgery and comparing at least two specimen extraction sites in terms of incidence of IH. Review of titles and abstracts from studies in the field identified by experts or included into existing reviews [ 12 14 ] allowed to develop a literature search strategy, which is reported in Table S2. Additional records will be identified by manual search of the reference lists of the included publications and existing reviews.…”
Section: Methods and Analysismentioning
confidence: 99%
“…20 Early reports included small case numbers. 2,[20][21][22] In 2009, Eshuis et al published a series of 10 cases using transcolonic, colonoscopic extraction of the specimen after ileocolic resection; they were successful in 8 out of 10 cases and noted difficulty when there was a larger inflammatory mass within the specimen. 23 Gardenbroek et al published a series of seven patients using a transrectal extraction after emergency total Minimally Invasive Colorectal Surgery Paruch 49 abdominal colectomy for inflammatory bowel disease.…”
Section: Natural Orifice Specimen Extractionmentioning
confidence: 99%
“…Selection of the location for extraction site incisions is driven by a multitude of patient, disease, and surgeon-related factors. The most commonly published specimen extraction site remains the midline incision, 2 although many datasets do not include this as a variable, making retrospective comparative studies difficult. More recently, many groups have also begun reporting results using natural orifice specimen extraction (NOSE) through transanal, transvaginal, and transcolonic routes.…”
mentioning
confidence: 99%